1988
DOI: 10.1002/art.1780310508
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of plasma anaphylatoxins in systemic lupus erythematosus predict flares of the disease and may elicit vascular injury in lupus cerebritis

Abstract: We measured levels of complement anaphylatoxin split products, C3a and C5a, in the circulation of patients with systemic lupus erythematosus (SLE). In 23 SLE patients who were followed serially, the mean C3a value was 179 ng/ml during stable disease and 550 ng/ml during a disease flare. In 10 patients, C3a levels predicted disease activity, with the C3a value rising from a mean of 183 ng/ml at a time of stable disease to a mean of 242 ng/ml 1-2 months prior to a clinical exacerbation of disease. The mean C3a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 33 publications
1
63
0
1
Order By: Relevance
“…Second, serum C3 and serum C4 have been widely used in attempts to monitor disease activity in SLE. Although the utility of these measurements is a subject of controversy, it is generally held that in some patients, particularly those with lupus nephritis, these are useful tests (3)(4)(5)10,13,14). Surprisingly, these tests have not been replaced or improved upon despite enormous advances in our understanding of complement biology during the last 20 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, serum C3 and serum C4 have been widely used in attempts to monitor disease activity in SLE. Although the utility of these measurements is a subject of controversy, it is generally held that in some patients, particularly those with lupus nephritis, these are useful tests (3)(4)(5)10,13,14). Surprisingly, these tests have not been replaced or improved upon despite enormous advances in our understanding of complement biology during the last 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although serum levels of C3, C4, and their activation-derived products are frequently used to monitor disease activity in SLE, their value as biomark-ers is a subject of controversy (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). These observations have led us to consider measurement of complement activation products bound to circulating blood cells (14,15).…”
mentioning
confidence: 99%
“…Fewer studies have actually addressed the predictive value of complement activation products (1,6). Hopkins and colleagues (6) reported that a rise in the C3a level at a time of stable disease predicted a disease flare 1-2 months later, in 10 patients who were followed up prospectively. In contrast, a fall in the C3 level occurred in only 7 of the 10 patients who had a subsequent disease flare, with the C3 value falling below the normal range in only 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, systemic complement activation, as reflected by increased serum levels of the anaphylatoxins, C3a and C5a, has been shown to correlate with CNS disease (12). Once complement activation occurs, it can lead to increased migration of cells toward the site of inflammation, alter the release of cytokines, and cause cell necrosis or apoptosis (3,13,14).…”
Section: H Uman Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%